Effect of Plant Types on Lodging Resistance and Yield of Field Pea (Pisum sativum L.) and Lodging Impact on Yield and Ascochyta Blight Severity - Yimam, Kedir; Yilma, Gizachew; Abo, Temesgen; Tesfaye, Deresa; Achenef, Gebyaw (International Journal of Bio-resource and Stress Management, 2024)
The present investigation was conducted during June–November, 2020 at Bekoji and Kofele, Ethiopia with the objective to analyse the effect of plant type on yield and lodging resistance potential and to assess the impact of lodging on ascochyta blight disease severity and seed yield of field pea. A total of 49 Field pea genotypes, representing two different plant types were evaluated for 13 characters using 7*7 simple lattice design. Plant types had significant effect on most of the studied traits. Considerable variation was observed for response against lodging and ascochyta blight with respect to plant types as well as genotypes even if high level of resistance was not identified. Normal leafed type had significantly higher lodging and ascochyta blight severity score than semi-leafless type. Even though the same plant type did not give the highest seed yield consistently in the two study locations, semi-leafless type did give significantly higher mean seed yield with 17% yield advantage over normal leafed type at Kofele. The regression analysis showed that lodging had negative significant influence on seed yield of field pea. Significantly largest yield reduction was observed by lodging in normal leafed type than in semi-leafless. The ascochyta blight severity was more increased by lodging in normal leafed type than the semi-leafless one. In other words genotypes with more susceptible to lodging were also susceptible to ascochyta blight with high yield reduction in normal leafed type. Thus, yield losses caused by ascochyta blight may be reduced by breeding for improved resistance to lodging.